Rethinking context : language as an interactive phenomenon. - Duranti, Alessandro; Goodwin, Charles (Studies in the social and cultural foundations of language, 1992)
The last decade has seen a fundamental rethinking of the concept of context. Rather than functioning solely as a constraint on linguistic performance, context is now also analyzed as a product of language use. In this new perspective, language and context are seen as interactively achieved phenomena, rather than predefined sets of forms and contents. The essays in this collection, written by many of the leading figures in the social sciences, critically reexamine the concept of context from a variety of different angles and propose new ways of thinking about it with reference to specific human activities such as face-to-face interaction, radio talk, medical diagnosis, political encounters and socialization practices. Each essay is prefaced by an introduction by the editors which provides relevant theoretical and methodological background and demonstrates its relation to other essays in the volume. The editorsā general introduction provides a lucid overview of the issues currently debated. Rethinking Context will be required reading for everyone working within the fields of linguistic anthropology, sociolinguistics, discourse analysis, pragmatics, conversation analysis and the sociology of language -- Description de l'éditeur.